2022
DOI: 10.17977/um048v28i2p57-65
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies Employed by Indonesian Virtual Exchange Students

Abstract: This study investigated the types of vocabulary learning strategies (VLS) employed by Indonesian college students. The study specifically aimed to find out (a) the most and the least frequently used VLS, and (b) the most useful VLS. A total of 105 nursing students who attended a virtual exchange program during the odd semester of 2021/2022 academic year participated in this study. This was ex post facto research which used a vocabulary learning strategy questionnaire to collect the data. To answer research que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…When students consult with their teachers or are involved with their peers to translate or explain the meaning of lexis that students do not know, it is a social strategy used in vocabulary learning strategies. This finding is consistent with the research found by Utomo et al (2022) who claimed that social strategies that ask others for clarification or information about difficult vocabulary can enhance language learning. Students can ask for definitions, synonyms, or translations of difficult vocabulary they do not know by asking their teacher or peers for help.…”
Section: The Challenges Of Animaker As Learning Mediasupporting
confidence: 92%
“…When students consult with their teachers or are involved with their peers to translate or explain the meaning of lexis that students do not know, it is a social strategy used in vocabulary learning strategies. This finding is consistent with the research found by Utomo et al (2022) who claimed that social strategies that ask others for clarification or information about difficult vocabulary can enhance language learning. Students can ask for definitions, synonyms, or translations of difficult vocabulary they do not know by asking their teacher or peers for help.…”
Section: The Challenges Of Animaker As Learning Mediasupporting
confidence: 92%